Malayan Banking Berhad (MAYBANK) / Nur Aiezaizzaty Mohd Nazri - Mohd Nazri, Nur Aiezaizzaty (Faculty of Business and Management, 2023)
Malayan Banking Group (Maybank) is Malaysian bank which built in 1960 a first located at Jalan Tun H S Lee, Kuala Lumpur. Maybank was created to give wide financial solution to all Malaysian, not only focusing on international business but cover financial need of financial consumer in Malaysia and small enterprises and businesses operates in Malaysia. Maybank’s network all over across 10 ASEAN countries and global financial centres have up to 2600 banking branches worldwide and more than 43, 000 employees. Maybank Group generally consist of five business pillar which represent by Group Community Financial Services, Group Global Banking, Group Islamic Banking and Group Insurance and Takaful. All these businesses group are support by six functions group which are Group Human Capital, Group Finance, Group Technology, Group Risk, Group Strategy and Innovation and Group Operation. Group Community Financial Services consists of eight line of businesses which are Commercial Banking, Mass Banking, Consumer Finance, Virtual Banking, Cards, Wealth Management and Retail Credit. GCFS line of businesses are supported by Finance (FRAN), Community Distribution, Strategy, Risk Management, Retail Branding Marcom and Business Compliance Control. Finance Group and MY CFS acts as business analytics, business cost management, performance management and distribution analytics, management information systems, management reporting and financial governance for Group Community Financial Services. Performance Management and distribution analytics tasks consist of Branches Incentive Planning, Branches Performance Management, CFS MY Balance Scorecards Management and CFS MY Townhall Management. Maybank Group has significant internal factors that influence their performance which are strengths and weaknesses. The performance of Maybank also affected by external factors such as opportunities and threats